The Finite Difference Method for the Periodic Boundary and Initial Value Problem of a Class of System of Generalized Zakharov Equations (Journal of Computational Mathematics, 2021)
This paper is intended to study the finite difference method for the periodic boundary and initial value problem of a class of system of generalized Zakharov equations.